A new Odontothrips species (Thysanoptera: Thripidae) from Iran - Mirab-Balou, Majid; Tong, Xiao-Li; Wang, Jun; Chen, Xue-Xin (Zootaxa, 2013)
Species of the Holartic genus Odontothrips Amyot & Serville (Thripidae: Thripinae) usually breed in the flowers of Fabaceae. Some species cause slight damage to Fabaceae crops (Pitkin 1972), and O. confusus Priesner sometimes produces high populations on alfalfa in Iran (Mirab-balou et al. 2013). The genus includes 31 species in the world (ThripsWiki 2013), of which four have been recorded from Iran (Mirab-balou and Chen 2011). Recently an undescribed species of Odontothrips was collected on flowers of alfalfa, and this is described below. Type specimens are deposited in the collection of Department of Plant Protection, College of Agriculture, Ilam University, Iran (ILAMU); and in the Insect Collection, Department of Entomology, South China Agricultural University, China (SCAU). Full nomenclatural information about Thysanoptera is available on the web (ThripsWiki 2013).